Study on the mechanism of water inrush disasters in overlying karst tunnels under damage-seepage coupling - LIN Zhibin; LI Yahao; LIN Peizhong; ZHANG Boyang; YANG Dafang (河南理工大学学报. 自然科学版)
ObjectivesTo analyze the impact of overlying karst caves on tunnels， this study investigates the law of water inrush disasters in overlying karst tunnels under damage-seepage coupling.MethodsBased on the Shuangbei Tunnel project in Chongqing， a rock mass damage-seepage coupling model is developed using the trilinear strain softening model. FLAC3D is employed to simulate the deformation， plastic zones， permeability coefficients， and water inflow of the surrounding rock during tunnel excavation through the overlying karst cave. The influence of rock mass damage-seepage coupling and varying karst cave water pressures on the water inrush disaster characteristics of the overlying karst tunnel is compared and analyzed.ResultsWhen the water pressure in the overlying karst cave is 1.8 MPa， after the tunnel excavation passes through the center of the overlying karst cave by 5.0 m， two “eight-shaped” water-conducting fracture zones form between the karst cave and the tunnel， causing the rock mass to slide by about 600 mm. The sliding body takes on an approximately trapezoidal shape， with top， bottom， and height dimensions of 3.6 m， 9.6 m， and 8.4 m， respectively. When the tunnel excavation does not pass through the overlying karst cave， the maximum water inflow does not exceed 0.01 m3/s. However， after passing 0 m， 2.5 m， and 5.0 m beyond the center of the overlying karst cave， the maximum water inflow reaches 0.022 m3/s， 0.185 m3/s， and 0.743 m3/s， respectively. For water pressures of 1.2 MPa， 1.8 MPa， and 2.4 MPa in the overlying karst cave， the maximum water inflows after passing through the cave are 0.031 m3/s， 0.0743 m3/s， 1.365 m3/s， respectively.ConclusionsDuring tunnel excavation through the overlying karst cave， if the water pressure in the cave exceeds the critical threshold， the tunnel will experience a roof collapse and water inrush accidents. The water inrush exhibits a certain delay and a large volume characteristic. The higher the water pressure of the karst cave， the earlier the water inrush occurs， and the greater the final water inflow. To accurately simulate the spatial and temporal evolution of water inrush disasters during karst tunnel excavation， the damage-seepage coupling effect in rock mass must be considered. The findings of this study provide an important insights for the stability control of surrounding rock in karst tunnel engineering.